Spatiotemporal evolution of SARS-CoV-2 Alpha and Delta variants during large nationwide outbreak of COVID-19, Vietnam, 2021 - Tam, NT; Anh, NT; Tung, TS; Thach, PN; Dung, NT; Trang, VD; Hung, LM; Dien, TC; Ngoc, NM; Van Duyet, L; Cuong, PM; Phuong, HVM; et al. (Centers for Disease Control and Prevention, 2023)
We analyzed 1,303 SARS-CoV-2 whole-genome sequences from Vietnam, and found the Alpha and Delta variants were responsible for a large nationwide outbreak of COVID-19 in 2021. The Delta variant was confined to the AY.57 lineage and caused >1.7 million infections and >32,000 deaths. Viral transmission was strongly affected by nonpharmaceutical interventions.